Entrepreneurship over Time: Measures of Activity and Recent Changes in the US: 1993-2002 - Paul Reynolds (Max Planck Institute for Research into Economic Systems, 2003)
Data from three different research programs, all measuring the prevalence rate of new firm creation in the US adult population, suggest that from 1993 to 2002 the level of entrepreneurship may have increased up to three fold, from 4 to over 13 percent of those 18-74 years of age–a shift from one in twenty adults to one in six adults. In 1993 entrepreneurial activity was more prevalent than marriages or parenting, by 2001 it was twice as common as marriages and parenting combined. Current evidence indicates that the high level of participation in start-ups in 1999-2002 was not reflected in the presence of new firms, suggesting that a smaller proportion of start-ups made the transition to an operating business. This may reflect a "rush to entrepreneur" among those with insufficient preparation or resources to successfully launch a new firm.
Keywords: 330; Unternehmer; Unternehmensgründung; USA